Peran Kearifan Lokal Lampung Piil Pesenggiri terhadap Pendidikan Karakter Peserta Didik di Lampung - Marilin Kristina; Ruly Nadian Sari (Attractive : Innovative Education Journal, 2024)
This research aims to find out the role of the values of local wisdom that exist in Lampung on the philosophy of Piil Pesenggiri towards the education of the character of the pupils. This research is qualitative research using the kind of literary study research. The data is obtained from library research. The data collection technique used by this researcher is a library study. Data analysis technique in this research using qualitative analysis techniques in a deductive way. The results of the research have been obtained that local wisdom in particular, has an important role in the formation of the character of the student if it is able to be integrated well into the learning process. The local wisdom values of Piil Pesenggiri which include Bejuluk Buadek, Nemui Nyimah, Nenggah Nyappur and Sakai Sambayan are integrated into the values found in character education: honesty, self-confidence, religious, caring, nationalist, independent, creative, santun, gotong royong, intelligent, competitive, positive thinking, responsibility, and tolerance.